2016
DOI: 10.1371/journal.pone.0148530
|View full text |Cite
|
Sign up to set email alerts
|

Systems Biology Approaches for the Prediction of Possible Role of Chlamydia pneumoniae Proteins in the Etiology of Lung Cancer

Abstract: Accumulating evidence has recently supported the association of bacterial infection with the growth and development of cancers, particularly in organs that are constantly exposed to bacteria such as the lungs, colon, cervical cancer etc. Our in silico study on the proteome of Chlamydia pneumoniae suggests an unprecedented idea of the etiology of lung cancer and have revealed that the infection of C. pneumoniae is associated with lung cancer development and growth. It is reasonable to assume that C. pneumoniae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…5 Various studies have shown that microbial alternations, characterized by a marked increase in the numbers of pathogens and a relative decrease in levels of beneficial bacteria, are connected with the development of gastrointestinal and extra-gastrointestinal cancers. [6][7][8][9][10][11][12][13] Altering the gut microbiota is expected as a novel method to deal with diseases associated with intestinal dysbiosis. Potential routes to target intestinal microbiota community include diet, probiotics, prebiotics, antibiotics and fecal microbiota transplantation (FMT).…”
Section: Introductionmentioning
confidence: 99%
“…5 Various studies have shown that microbial alternations, characterized by a marked increase in the numbers of pathogens and a relative decrease in levels of beneficial bacteria, are connected with the development of gastrointestinal and extra-gastrointestinal cancers. [6][7][8][9][10][11][12][13] Altering the gut microbiota is expected as a novel method to deal with diseases associated with intestinal dysbiosis. Potential routes to target intestinal microbiota community include diet, probiotics, prebiotics, antibiotics and fecal microbiota transplantation (FMT).…”
Section: Introductionmentioning
confidence: 99%
“…While studies targeting at the direct relationship between lung cancer and lung microbiome are quite limited at present, there have been interesting studies documenting persistent lung infections and inflammation can favor carcinogenesis . And certain types of microbial agents or products may positively or negatively modulate lung cancer development and/or progression .…”
Section: Introductionmentioning
confidence: 99%
“…While studies targeting at the direct relationship between lung cancer and lung microbiome are quite limited at present, there have been interesting studies documenting persistent lung infections and inflammation can favor carcinogenesis. [25][26][27][28][29][30][31][32] And certain types of microbial agents or products may positively or negatively modulate lung cancer development and/or progression. 27,30,32,33 A large epidemiological study in humans suggested that the frequency of lung cancer increases upon use of repeated courses of antibiotics providing circumstantial evidence that some links may exist between the bacterial microbiota and lung cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of infectious agents in the etiology of different types of cancer has piqued the interest of scientists in recent years. Recent data have shown the involvement of Mycoplasma hominis, Chlamydia pneumoniae, and Escherichia coli infection in the etiology of prostate cancer, lung cancer, and colon cancer, respectively [9][10][11][12]. Recently, a wealth of previous studies have reported that microRNAs (miRNAs), a class of noncoding RNAs characterized by approximately 22 nucleotides in length, can inhibit the stability and translation of messenger RNAs (mRNAs) through binding to the specific sequence of genes, which are used as potential biomarkers for different kinds of cancer.…”
Section: Introductionmentioning
confidence: 99%